Once The Buddha Was Born as Keanu Reeves: The Shaping of Buddhism in American Film and Popular Culture. - Suh, Sharon A. (Cross Currents, 2020)
The article focuses on Buddhism in American motion pictures and popular culture by mentioning about actor Keanu Reeves as Buddha in the film "Little Buddha" directed by Bernardo Bertolucci. Topics discussed include the film Bill & Ted's Excellent Adventure; sequels of the film The Matrix and mythical references as religious symbolism.